Research Priorities Perceived by Agricultural Education Post-Graduates in Eswatini - Alfred F. Tsikati (International Journal of Social Sciences: Current and Future Research Trends, 2023)
There is a need for Agricultural Education researchers to investigate where the discipline has been in order to focus future research. However, no study has been conducted to identify research priority areas for Agricultural Education in Eswatini. Thus, this study sought to identify research priority areas for Agricultural Education in Eswatini. This was a descriptive survey targeting a census of master’s degree graduates (N=48), completed from 1996 to 2017 in Agricultural Education at the University of Eswatini. Validity of the instrument was ensured through the use of five experts from the Department of Agricultural Education and Extension (AEE), Faculty of Agriculture at the University of Eswatini (UNESWA). The inter-item reliability was determined using Cronbach’s Alpha and the reliability coefficient was found to be r=.986 meaning the questionnaire was 98.6% reliable. Data analysis was performed using descriptive and inferential statistics. Findings of the study revealed that all the primary and secondary themes were research priorities. The leading primary research theme was Delivery methodologies while secondary research theme was Creative thinking and problem-solving. Therefore, the study concluded that research in agriculture must be informed and guided by the research priority areas established in the study. Consequently, Agricultural Education discipline in the Kingdom of Eswatini needs to have a research agenda that will be directed by the research priorities established in this study.